Doprowadź do najprostszej postaci (daje naj)

-3(2y-3x)+2(3y+2x)=

-4(x-5y)-3(2y-x)=

-x(z-y)-z(-x+y)=

4(x+y)-2(x-y)-3x(1+y)=​



Odpowiedź :

Odpowiedź:

-3(2y - 3x) + 2(3y + 2x) =  -6y + 9x + 6y + 4x = 13x  

-4(x - 5y) - 3(2y - x) = -4x + 20y - 6y + 3x = -x + 14y

-x(z - y) - z(-x + y) = -xz + xy + xz - yz = xy - yz

4(x + y) - 2(x - y) - 3x(1 + y) = 4x + 4y - 2x + 2y - 3x - 3xy = -x + 6y - 3xy​

Szczegółowe wyjaśnienie:

[tex]1)-3(2y-3x)+2(3y+2x)=-6y+9x+6y+4x=13x\\2)-4(x-5y)-3(2y-x)=-4x+20y-6y+3x=-x+14y\\3)-x(z-y)-z(-x+y)=-xz+xy+2x-2y\\4)4(x+y)-2(x-y)-3(1+y)=4x+4y-2x+2y-3-3y=2x+3y-3[/tex]